Rational design of NiCo2O4/g-C3N4 composite as practical anode of lithium-ion batteries with outstanding electrochemical performance from multiple aspects - Liu, Yu; He, Shuai; Zhong, Yijun; Xu, Xiaomin; Shao, Zongping (ELSEVIER SCIENCE SA, 2019)
The spinel oxide NiCo2O4 is regarded as a desirable electrode material in lithium-ion batteries with high performance due to its better electrochemical activity and higher capacity compared to traditional simple oxides. However, lithium-ion batteries with this conversion reaction anode still suffer from low initial Coulombic efficiency accompanied by the generation of solid electrolyte interface layer. Herein, a facile strategy is proposed to couple nanoparticulate NiCo2O4 with g-C3N4, which effectively reduces solid electrolyte interface formation and leads to a high initial Coulombic efficiency. Various characterization techniques confirm that NiCo2O4 nanoparticles grow homogeneously on g-C3N4 nanosheets. This NiCo2O4/g-C3N4 hybrid, as an anode material for lithium-ion batteries, can reach an initial Coulombic efficiency of 84.5%, which is attributed to low interfacial surface area and high discharge potential of electrodes. Owing to the synergistic effect in the NiCo2O4/g-C3N4 hybrid, excellent reversible capacities of 1252 and 476 mAh g−1 are maintained at respective current densities of 100 and 500 mA g−1 after 100 cycles. The highly reversible lithium storage is a result of high NiCo2O4 electrode performance, unique layered structure, and excellent g-C3N4 properties.